COVID-19 dan Tuberkulosis Paru, Antara Koinfeksi dan Reaktivasi dari Laten Tuberkulosis: Sebuah Kajian Sistematis - Arya Marganda Simanjuntak; Indra Yovi; Patricia Dean Ully Marbun; Adinda Elisabet (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Introduction: Globally, cases of pulmonary tuberculosis (PTB) are rising by 4%, while new cases have declined in many nations, most notably by 14% in Indonesia. During the COVID-19 pandemic, the number of undiagnosed and untreated PTB patients could rise and infect more people. In particular, CD8+ lymphocytes were decreased in COVID-19. Perhaps this is the cause of the rise in cases, but there is no data to show it. Aim: Determine current data about the PTB with COVID-19 coinfection and possible reactivation of PTB after COVID-19 infection in LTB patient. Methods: This systematic review is based on PRISMA statements using Pubmed, EBSCOHost, Science Direct and Cochrane from December 2019 to July 2022. Inclusion and exclusion criteria were set to select studies that included. We analyze risk of bias of all included studies with JBI critical appraisal tools. Results: This study had 107,425 patients in total from 20 studies. All studies were deemed to have low overall author bias risks. A critical component of PTB defense is CD8+. By reducing lymphocytes, COVID-19 can encourage the growth of PTB, which might therefore result in coinfection or the reactivation of existing PTB. Conclusion: COVID-19 possibly increase case of PTB in form of co-infection or reactivation of PTB in LTB patients. This needs special attention for patients that have infected by COVID-19 to followed up for risk developing PTB.